Optimizing Photovoltaic Performance in p-Cu2O/n-TiO2 Heterojunction Solar Cells: The Impact of Annealing Temperature, Layer Thickness, and Carbon Doping - Pakpahan, Sarinah; Gultom, Rimawanto (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
This study analyzes the photoresponse behavior and optimizing the efficiency of p-Cu₂O/n-TiO₂ heterojunction solar cells. The impact of annealing temperature, layered thickness, and carbon doping on the optical and electrical characteristics of the solar cells was investigated. The findings reveal that the annealing temperature continuously affects the optical absorption and energy gap of Cu2O, with the best performance at 250°C. Increasing the layer thickness of Cu2O resulted in further improvement in absorption and efficiency. It was also found that doping carbon into TiO2 lowered the energy gap, increasing efficiency. The maximum efficiency of 0.003593% was obtained with carbon-doped TiO2. This work guides optimizing the design of heterojunction solar cells for better photovoltaic performance.